Pengaruh Inisiasi Menyusu Dini Terhadap Pemberhentian Perdarahan Post Partum Di Puskesmas Tiganderket Kec. Tiganderket Kab. Karo Tahun 2023 - Natalina Perangin angina; Kamelia Sinaga; Imran Saputra Surbakti (Lembaga Pengembangan Kinerja Dosen, 2023)
Mortality and morbidity in pregnant women is a serious problem for the world. The causes of maternal death are quite complex problems, which can be classified based on reproductive factors, obstetric complications, health services and economics. The government program, namely early initiation of breastfeeding or breastfeeding after giving birth for the first time, can provide many benefits for babies and mothers so that maternal and infant mortality rates can be reduced with the early initiation of breastfeeding program. This study aims to determine the effect of early initiation of breastfeeding on stopping post partum bleeding at the Tiganderket District Health Center. Tiganderket, Karo Regency. This type of research is quantitative research using a pre-designed experiment with a statistical comparison group approach / control group design only post test, and analyzed using an independent t test. Data collection uses primary and secondary data. The respondents of this research were 16 mothers who gave birth at the Tiganderket District Health Center. Tiganderket, Karo Regency The results of this study show that the average number of fourth stage blood deliveries between mothers who were given early breastfeeding initiation and mothers who were not given early breastfeeding initiation was obtained where p=0.000 so p<0.005, then Ho was rejected and Ha was accepted ..The conclusion is that there is an effect of early initiation of breastfeeding on stopping post partum bleeding at the Tiganderket District Health Center. Tiganderket, Kab. Karo in 2023